Techniques for Detection of Trichothecene in Food: A Comprehensive Review - Iqbal, Sadia; Sajid, Syeda Azka; Ali, Muhammad; Mushtaq, Noor; Sultan, Muhammad Wasif; Mushtaq, Mehvish; Tahir, Tehreem; Mohsin, Javaria; Shafiq, Iqra; Muzaffar, Usman (Formosa Journal of Science and Technology, 2025)
Trichothecenes, pose significant health risks to humans and animals by contaminating food and feed. These toxins are classified into Type A and Type B. Type A trichothecenes are commonly detected in various food matrices, while Type B trichothecenes contaminate crops and are linked to alimentary toxicities, including emetic reactions. Advanced detection methods such as liquid chromatography-tandem mass spectrometry are widely used. Biological controls, such as Debaryomyces hansenii, have shown promise, reducing toxin content and suppressing pathogen spread. Trichothecenes exhibit ribotoxic, pro-inflammatory, and cytotoxic effects, making their management a critical focus in food safety. This review comprehensively explores detection techniques, management strategies, and the impact of trichothecene contamination on human health, emphasizing its relevance in public policy and food security.